Hambatan Penegakan Hukum Pidana Lingkungan bagi Pelaku Pembuangan Air Limbah pada Rumah Pemotongan Hewan di Kota Kupang - Julio Rihi Nawa; Jimmy Pello; Thelma S.M. Kadja (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Environmental protection and improving industrial waste management, including slaughterhouses, are crucial to maintaining ecosystem balance and ensuring human health and welfare in the future. Good implementation of regulations and strict law enforcement are steps. The problem formulation in this research is: (1) What are the efforts of the Kupang City government in processing waste water at the Slaughterhouse in Kupang City? (2) What are the government's obstacles in enforcing criminal acts for perpetrators of waste water disposal at slaughterhouses in Kupang City? This research is Empirical Juridical Legal Research. This research uses data collection methods using interview techniques at the relevant department. The results of this research show: (1) Pollution due to waste water from slaughterhouses is a serious environmental problem in Kupang City. This article discusses the efforts made by the Kupang City government to overcome this problem. These efforts include routine monitoring and inspections to ensure compliance with regulations, strict law enforcement against violations, as well as education and outreach to the public about the importance of good waste management. (2) Law enforcement against perpetrators of waste water disposal at slaughterhouses is a complex challenge for the government. Apart from that, other challenges are less than optimal coordination between relevant agencies, as well as political and economic factors that influence law enforcement policies. By understanding these obstacles in depth, it is hoped that effective solutions can be found to increase the effectiveness of law enforcement against perpetrators of waste water disposal in slaughterhouses in order to maintain environmental sustainability.